2017
DOI: 10.1038/srep43294
|View full text |Cite
|
Sign up to set email alerts
|

Personalized chemotherapy selection for breast cancer using gene expression profiles

Abstract: Choosing the optimal chemotherapy regimen is still an unmet medical need for breast cancer patients. In this study, we reanalyzed data from seven independent data sets with totally 1079 breast cancer patients. The patients were treated with three different types of commonly used neoadjuvant chemotherapies: anthracycline alone, anthracycline plus paclitaxel, and anthracycline plus docetaxel. We developed random forest models with variable selection using both genetic and clinical variables to predict the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…[ 30 ] method, which used Support Vector Machine approach as a base; (iii) Yu et al. [ 31 ] method, also referred to as Personalized REgimen Selection (PRES), which used random forest approach as a base; and (iv) mRNA expression alone (without taking into account information about molecular pathways) ( see Materials and Methods ). To assure that all methods are comparable to our pathway-centric method, we trained Epsi et al., Zhong et al., Yu et al., and expression-only methods on the Training cohort, with each producing a list of predictions, either pathways or gene lists, depending on the method (112 predictions for Epsi et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 30 ] method, which used Support Vector Machine approach as a base; (iii) Yu et al. [ 31 ] method, also referred to as Personalized REgimen Selection (PRES), which used random forest approach as a base; and (iv) mRNA expression alone (without taking into account information about molecular pathways) ( see Materials and Methods ). To assure that all methods are comparable to our pathway-centric method, we trained Epsi et al., Zhong et al., Yu et al., and expression-only methods on the Training cohort, with each producing a list of predictions, either pathways or gene lists, depending on the method (112 predictions for Epsi et al.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the advantages of our approach over other commonly used techniques, we compared its performance to (i) extreme-responder analysis, described in Epsi et al. [ 28 ]; (ii) SVM-based method [ 30 ]; (iii) PRES random forest-based method [ 31 ]; and (iv) expression data alone (without utilizing biological pathways). In each case, we utilized Training cohort for model training and Test cohort 1 for model validation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As statistical approaches, multivariable logistic regression has been used for binary outcomes such as metastasis 16 . As machine-learning methods, artificial neural networks, Bayesian networks, support vector machines (SVMs), and decision trees (DTs) are typical methods for binary outcomes 17 , and machine learning-based analyses have been applied to the prediction of cancer prognosis [17][18][19] . Combining multiple methods has also been reported, such as ReliefF-GA-ANFIS 18 .…”
mentioning
confidence: 99%
“…It has been shown that gene expression is very informative and highly predictive of various clinical outcomes, such as the status of biomarkers [15][16][17][18][19][20][21], tumor types/status [22][23][24][25], the risks of recurrence [26,27] and survival [27][28][29][30], and therapeutic response [4,[31][32][33][34]. For gene expression data, the gene expression profiles themselves, therefore, are ideally suited for inferring the missing metadata.…”
mentioning
confidence: 99%